Hilabi, A Integrating Islamic Values and Environmental Awareness in Madrasah Education: The Ecomadrasah - Abdurrahman hilabi; Miftahul Ulum (CV. Kayaswara, 2025)
The global environmental crisis demands a strategic role for education in building sustainable ecological awareness, including thru Islamic religious education that is oriented toward moral values and environmental ethics. This research aims to examine the concept of Ecomadrasah as an integrative model that combines Islamic religious education with environmental awareness to develop students who are both religious and concerned about environmental sustainability. This study employs a library research approach, analyzing various scientific articles, academic books, policy documents, and relevant previous research findings related to Islamic religious education and environmental education. Data were analyzed using content analysis techniques to identify concepts, patterns, and the implications of implementing Ecomadrasah in the context of madrasah education. The study results indicate that integrating Islamic values such as trust (amanah), balance (mizan), and the prohibition of causing damage on earth (fasad) into the Islamic religious education curriculum can increase students' ecological awareness. The implementation of Ecomadrasah, including thru P5RA, encourages the formation of environmentally friendly behavior thru greening activities, waste management, climate change education, and environmental-based entrepreneurship. This research concludes that Ecomadrasah has significant potential as a contextual and relevant model of Islamic education in supporting sustainable development, although it still faces challenges in terms of supervision and public acceptance.